EMIGRANT ABOUT EMIGRANTS. OSKAR MIŁOSZ AND JOSIF BRODSKI’S FLAWLESS PORTRAITS - Czyżak, Agnieszka (Porównania, 2017)
This article is an analysis of associations between the portraits of other poets created by Czesław Miłosz, namely Oskar Miłosz and Josif Brodzki, and his self-portraits. The starting point is the experience of emigrant life treated as an unusual existential challenge. Miłosz’s biography, created by him in exile as a “biography of a great national poet” and simultaneously “the biography of a world poet” demands context of similar life-histories: emigrant poets from Eastern Europe successfully forming their literary careers out of homeland. However, the most important connection between those poets is – in Miłosz’s writing – “the hierarchy”, interpreted as a resistance against relativism and as an inflexible belief about the necessity of differentiation between that which is high and that which is low.